On the regions of implementation of the heterogeneous equilibrium laws and the law of mass action - L. A. Serafimov; A. K. Frolkova (Тонкие химические технологии, 2012)
Some laws of heterogeneous equilibrium and the law of mass action are considered. The regions of implementation of these laws are shown.